Novel approach of cutting temperature measurement in sustainable milling of Ti-6Al-4V alloy. (15th June 2023) - Jamil, Muhammad; He, Ning; Zhao, Wei; Kumar Gupta, Munish; Mashood Khan, Aqib
Highlights: Thermal modelling has been performed under novel hybrid coolant/lubricant. FEM simulations were carried out using DEFORM® software. Initially, the 2D milling models were developed and measurements were performed. The comparison of simulations and experimental results showed a maximum error of 2.5 % for cutting temperature. Abstract: Ti-6Al-4V alloy has widespread uses in a variety of engineering applications such as in the manufacturing of aerospace, automotive, and prosthetics body-parts owing to its unique characteristics. However, the machining of Ti-6Al-4V generates high cutting temperature due to poor thermal conductivity. This high cutting temperature triggers chemical reactivity of the alloy with the tool material and accelerates the edge wear. Therefore, the cryogenic coolants are used to improve the cutting performance, but their poor lubrication allows for high cutting forces. Hybrid lubri-coolants could be an alternative to reduce the temperature efficiently. The simulation of hybrid lubri-coolants by Finite Element Modeling (FEM) is an interesting to explore the high-performance cutting of hard titanium alloy. The current study compares the cutting temperatures using DEFORM® FEM simulations software and to foresee the cutting temperatures in milling Ti-6Al-4V at various levels of cutting speeds Vc (100–300 m/min), and feed per tooth fz 0.08–0.12 mm/z and under effect of hybrid lubri-coolants (ethanol, ester oil, and hybrid ethanol-ester oil). Initially, the 2D milling models were developed and predicted results were compared to milling experiments. The comparison of experimental and simulation cutting temperatures revealed a maximum of 6.5 % error. Thus, it can be concluded that 2D modeling is an effective tool to predict the milling temperatures within a reasonable error.